Pozbawienie władzy rodzicielskiej w polskim porządku prawnym - Nowicka, Urszula (Ius Matrimoniale, 2017)
The Family and Guardianship Code regulates the legal institutions of deprivation of parental authority. The subject of the article is therefore an analysis of this institution in the Polish legal order. It is a very important institution and is the most severe interference in a family’s life under Polish law, it is the most rigorous measure a court can apply to a parent who can not or does not want to exercise his parental authority appropriately. When resorting to such measures the courts should first of all act upon the principle of wellbeing of the child that amounts to one of the most precious values enshrined in the legal system.